Bronchiectasis associated with electronic cigarette use: A case series. Issue 12 (21st October 2020) - Mull, Eric S.; Shell, Richard; Adler, Brent; Holtzlander, Melissa
Abstract: Bronchiectasis (BE) is defined as a permanent, irreversible dilation of the bronchial tree. In the pediatric population, this disease process is most commonly associated with patients with cystic fibrosis (CF). However, BE unrelated to CF is increasingly noted as a cause of chronic respiratory related morbidity worldwide. Chronic inflammation and recurrent infection result in cellular cascades that lead to irreversible structural changes of the airways. When these architectural changes occur, they confer extensive risks to morbidity usually due to continued infections. In the adult population, BE has been associated with chronic obstructive pulmonary disease, which is mainly caused by cigarette smoking. In this report, the authors reviewed various cases of BE in the pediatric population at our institution. After a comprehensive case by case review, we compiled details of three cases of newly diagnosed BE where the most likely inciting factor was the electronic cigarette use. Common features of the three cases included at least a year of e‐cigarette use with conjunction of tetrahydrocannabinol and radiologic findings of BE, ground glass opacities, and nodule formation.